2020
DOI: 10.3892/or.2020.7770
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SERPINE1 reverses resistance of triple‑negative breast cancer to paclitaxel via suppression of VEGFA

Abstract: Breast cancer (BC) has a poor prognosis and a high number of visceral metastases. Serine protease inhibitor, clade E member 1 (SERPINE1) is a molecule involved in several human malignancies. However, it remains unknown if SERPINE1 plays a role in the development of taxane resistance in TNBC cells. In the present study, the role and mechanism of SERPINE1 in the development of paclitaxel (PTX) resistance in TNBC cells were investigated. A bioinformatics analysis of gene expression profiles in PTX-resistant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 59 publications
(65 reference statements)
1
44
0
Order By: Relevance
“…In estrogen receptor (ER)-negative breast cancer, it has been indicated that ATF4 can activate the expression of the oncogene PSAT1 and promote cell proliferation [ 40 ]. Knockdown of SERPINE1 was found to significantly inhibit cell survival and induce apoptosis of breast cancer cells in vitro [ 41 ]. SESN2 is involved in the suppression of genesis of breast cancer genesis through its interaction with AMP-activated protein kinase (AMPK) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In estrogen receptor (ER)-negative breast cancer, it has been indicated that ATF4 can activate the expression of the oncogene PSAT1 and promote cell proliferation [ 40 ]. Knockdown of SERPINE1 was found to significantly inhibit cell survival and induce apoptosis of breast cancer cells in vitro [ 41 ]. SESN2 is involved in the suppression of genesis of breast cancer genesis through its interaction with AMP-activated protein kinase (AMPK) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…SERPINE1 may have a role in the establishment of the disease. Indeed, SERPINE1 has been reported to be involved in angiogenesis, observed as enriched in MF tissues compared to M, and tumorigenesis [ 47 ]. Based on this, SERPINE1 expression in the myometrium could be used for early diagnosis of the disease and as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINE1 is a fibrinolytic inhibitor that has been involved in several human tumor malignancies. For example, SERPINE1 has been indicated to be associated with PTX resistance of breast cancer [ 31 ], and LncRNA LINC00200 promotes the progression of gastric cancer by regulating miR-143-3p/SERPINE1 axis [ 32 ]. Li et, al have reported that CEP72 induces bladder urothelial carcinoma cell aggressiveness by overexpression of SERPINE1 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%